STAFFING GAP ANALYSIS FOR CONCRETE PUMP TECHNICIANS: A WLA AND FTE APPROACH IN THE HEAVY EQUIPMENT RENTAL INDUSTRY - Muhammad Nursyamsu Alhafidh; Anik Dwiastuti; Rudi Nurdiansyah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Ensuring operational efficiency in the heavy equipment rental business requires a precise alignment between equipment availability and workforce capacity, particularly for concrete pump technicians operating across demanding project sites. This study addresses the empirical gap in technician staffing adequacy by applying Workload Analysis (WLA) and Full-Time Equivalent (FTE) within a heavy equipment rental company. Activity data from five technicians were collected through structured interviews and verified through layered validation involving HRD judgment, managerial review, and company work reports. The analysis produced a total annual workload of 6,221.25 hours, equivalent to 3.31 FTE, quantifying an overstaffing condition in which individual FTE values ranged from 0.60 to 0.71, all classified as underload. Scenario analysis further demonstrated that a staffing level of three technicians yields an FTE of 1.10, the only configuration falling within the normal workload range. These findings extend the application of WLA and FTE to concrete pump maintenance in heavy equipment rental, a context that remains limited in prior workforce planning literature, and demonstrate the value of multi-layered data validation in improving the accuracy of workforce requirement assessments.